PENGARUH PAJAK DAN UKURAN PERUSAHAAN TERHADAP TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI 2017-2020 - Ridelni Eunike Br Ginting; Lorina Siregar Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This study aims to analyze and see how the effect of Tax and Size Firm on Transfer Pricing. The research data were obtained from manufacturing companies in the food and beverage sub-sector which are listed on the Indonesia Stock Exchange. Population this study uses financial statements of manufacturing companies in the food and beverage sub-sektor in 2017-2020 which are listed on the Indonesia Stock Exchange as the population. The sample used is 9 companies for 4 years and total sample is 36 observation data. Processin data using SPSS and performing several stateges of analysis is descriptive statistical test, normality test, multicolinearity test, heteroscedasticity test, autocorrelation test, determination test, T test and F test, The results of this study indicate that partially tax have no effect on transfer pricing. In contrast to the size firm which partially have a significant effect on transfer pricing. While simultaneously taxes and size firm have a significant effect on transfer pricing.